Endovascular thrombectomy 2020: open issues - Lanzer, Peter; Widimsky, Petr; Gorog, Diana A; Mazighi, Mikael; Liebeskind, David; Cognard, Christophe (European heart journal supplements, 2020)
Mechanical thrombectomy is now well - established first - line treatment for selected patients with large artery occlusions of the anterior circulation. However, number of technical and procedural issues remains open to assure optimal outcomes in majority of patients including those suffering from posterior circulation perfusion defects. This brief review addresses some of the open issues and refers to the ongoing trials to close the existing knowledge gaps.
Keywords: agenda 2020; state-of-the-art; acute ischemic stroke; Mechanical thrombectomy